The effects of autocatalyst copper coating of SiCp on the microstructure of CuSiCp composites - Azmi, Kamardin; Mohd Nazree, Derman; Shaiful Rizam Shamsudin; Mazlee, Mohd Noor; J.A.H., Iqwan (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.